2008
DOI: 10.1080/10641950701826158
|View full text |Cite
|
Sign up to set email alerts
|

Altered Potassium Channel Expression in the Human Placental Vasculature of Pregnancies Complicated by Fetal Growth Restriction

Abstract: The gene expression of two voltage-gated K channels thought to be important for altered vascular reactivity following changes in oxygenation is increased in FGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“… G, gene; R, mRNA; P, protein; 1, Amberg and Santana (2006) ; 2, Archer et al (2004) ; 3, Bergren et al (2009) ; 4, Bocksteins et al (2009) ; 5, Brahmajothi et al (1996) ; 6, Castellano et al (1997) ; 7, Chen et al (2010) ; 8, Cioli et al (2014) ; 9, Corcoran et al (2008) ; 10, Costigan et al (2010) ; 11, Czirják et al (2007) ; 12, Davies and Kozlowski (2001) ; 13, Drewe et al (1992) ; 14, Georgiev et al (2012) ; 15, Georgiev et al (2014) ; 16, Fantozzi et al (2006) ; 17, Firth et al (2011) ; 18, Friedland et al (2007) ; 19, Friedman et al (2013) ; 20, Fyfe et al (2012) ; 21, Hayama et al (2006) ; 22, Hölter et al (2012) ; 23, Hugnot et al (1996) ; 24, Jorge et al (2011) ; 25, Hristov et al (2012b) ; 26, Hristov et al (2012a) ; 27, Lee et al (2003) ; 28, Lee et al (2015) ; 29, Li et al (2015) ; 30, Mederos y Schnitzler et al (2009) ; 31, Moreno-Domínguez et al (2009) ; 32, Müller et al (2014) ; 33, Ottschytsch et al (2002) ; 34, Patel et al (1997) ; 35, Platoshyn et al (2004) ; 36, Rao et al (2002) ; 37, Salinas et al (1997b) ; 38, Sandberg et al (2014) ; 39, Sano et al (2002a) ; 40, Sano et al (2002b) ; 41, Shepard and Rae (1999) ; 42, Spitzner et al (2007) ; 43, Stocker and Kerschensteiner (1998) ; 44, Su et al (1997) ; 45, Suzuki and Takimoto (2004) ; 46, Thorneloe and Nelson (2003) ; 47, Tsantoulas et al (2012) ; 48, …”
Section: Physiological Role Of Kv2/kvs Heterotetramers In Different Tmentioning
confidence: 99%
“… G, gene; R, mRNA; P, protein; 1, Amberg and Santana (2006) ; 2, Archer et al (2004) ; 3, Bergren et al (2009) ; 4, Bocksteins et al (2009) ; 5, Brahmajothi et al (1996) ; 6, Castellano et al (1997) ; 7, Chen et al (2010) ; 8, Cioli et al (2014) ; 9, Corcoran et al (2008) ; 10, Costigan et al (2010) ; 11, Czirják et al (2007) ; 12, Davies and Kozlowski (2001) ; 13, Drewe et al (1992) ; 14, Georgiev et al (2012) ; 15, Georgiev et al (2014) ; 16, Fantozzi et al (2006) ; 17, Firth et al (2011) ; 18, Friedland et al (2007) ; 19, Friedman et al (2013) ; 20, Fyfe et al (2012) ; 21, Hayama et al (2006) ; 22, Hölter et al (2012) ; 23, Hugnot et al (1996) ; 24, Jorge et al (2011) ; 25, Hristov et al (2012b) ; 26, Hristov et al (2012a) ; 27, Lee et al (2003) ; 28, Lee et al (2015) ; 29, Li et al (2015) ; 30, Mederos y Schnitzler et al (2009) ; 31, Moreno-Domínguez et al (2009) ; 32, Müller et al (2014) ; 33, Ottschytsch et al (2002) ; 34, Patel et al (1997) ; 35, Platoshyn et al (2004) ; 36, Rao et al (2002) ; 37, Salinas et al (1997b) ; 38, Sandberg et al (2014) ; 39, Sano et al (2002a) ; 40, Sano et al (2002b) ; 41, Shepard and Rae (1999) ; 42, Spitzner et al (2007) ; 43, Stocker and Kerschensteiner (1998) ; 44, Su et al (1997) ; 45, Suzuki and Takimoto (2004) ; 46, Thorneloe and Nelson (2003) ; 47, Tsantoulas et al (2012) ; 48, …”
Section: Physiological Role Of Kv2/kvs Heterotetramers In Different Tmentioning
confidence: 99%
“…Similar to other oxygen-sensitive vasculature, potassium channels are main determinants of vascular resistance (Wareing and Greenwood, 2011) and vasculogenesis (Brereton et al, 2013) in chorionic plate vessels. Previous studies have not been conclusive for the role of these channels in complicated pregnancies, but some authors suggests that K(V) may be involved in IUGR (Corcoran et al, 2008) and ROS might be regulating their function in the placenta (Mills et al, 2009), elevating vascular resistance. Furthermore, it has been shown that ROS enhanced basal tension and vasoconstriction in response to a thromboxane mimetic (Mills et al, 2009).…”
Section: Hypoxia and Oxidative Stressmentioning
confidence: 99%
“…28,29 Focusing on pregnancy-associated pathologies, K þ channels have been implicated in preeclampsia, gestational diabetes, and fetal growth restriction. The majority of these reports are focused on placenta, 30 fetoplacental vessels, 26 and maternal uterine vessels, 31 the knowledge of umbilical cord vessels being more scarce, regardless of the fact that their morphometric characteristics as well as blood flow parameters have been demonstrated to be altered in these pathologies. 32,33 In particular, it has been reported that the role of K IR and BK Ca channels may be altered in HUA coming from gestational diabetes mellitus and pregnancy-induced hypertension, respectively.…”
Section: Implication Of K þ Channels In Pregnancy-related Pathologiesmentioning
confidence: 99%